Analisis Efektivitas Remote Audit dan Agility Audit Dalam Mendeteksi Missappropriation Of Assets Pasca Pandemi (Jurnal Kendali Akuntansi, 2024)
The era of digitalization has brought progress in the field of accounting through the use of various new technologies, but it has also brought new challenges and potential threats related to data security and integrity. Misappropriation of Assets is one of the problems that may arise. Cases occur when internal or external parties steal financial data or access identity information to manipulate accounts or access company assets. This research is research that applies qualitative descriptive methods. The aim of this research is to find out and analyze the effectiveness of remote audits and agility audits in detecting misappropriation of assets that emerged in the post-Covid-19 pandemic. The type of data in this research is qualitative. The data source for this research is secondary data. Remote audit and agility audit represent a paradigm shift in audit practice from traditional to modern. Remote Audit allows the audit process to be carried out remotely, which is increasingly important in technological transformation. Meanwhile, audit agility focuses on increasing the ability to respond to change and efficiency in the audit process. Remote audits can provide efficiency and effectiveness in the audit process, provided that the process is supported by both the auditor and the audited party. In addition, this approach allows auditors to carry out analytical procedures with electronic evidence, interactions with auditees, and reporting that contains reliable financial data.